Photodegradation of the Pentaerythritol Wastewater Catalyzed by TiO2 - Bai, Guoyi; Shi, Minyu; Zhang, Liang (Asian Journal of Chemistry, 2010)
The photodegradation of pentaerythritol wastewater catalyzed by TiO2 was studied in this report. The rutile phase TiO2-HY with a particle size of 22.6 nm showed the highest degradation efficiency of 90.5 % in solar light under the optimal operating conditions, while the pH value was 6 and the amount of catalyst was 0.06 g.